Values, Motivations, and Intentions to Engage in Proenvironmental Behavior. Issue 4 (May 2020) - van Riper, Carena J.; Lum, Clinton; Kyle, Gerard T.; Wallen, Kenneth E.; Absher, James; Landon, Adam C.
Knowledge of the relationships among psychological constructs such as values and motivations that influence proenvironmental behavior provides public land management agencies with guidance on how to minimize stakeholder impacts on the environment. A rich body of research has demonstrated that values form a tripartite structure underlying environmental concern, encompassing biospheric, egoistic, and altruistic values; however, recent work has suggested hedonic values are also an instrumental basis for environmental concern. Few studies have tested this proposition. We contend that hedonic values are instrumental in explaining the psychological processes that gird individual decisions, particularly in nature-based settings where stakeholder decisions are compelled by leisure pursuits. Our results indicate that place-based motivations, particularly escape from the pressures of everyday life, can help close the prominent value–action gap and explain why outdoor recreationists engage in minimum-impact activities specified in the U.S. Leave No Trace educational outreach program.